Investigation of the Effect of Enamel Matrix Protein, Platelet-Rich Fibrin, and Bone Graft on New Bone Formation in Guided Tissue Regeneration in Rat Calvarium - Donmezer, Tugce; Talo Yildirim, Tuba; Dundar, Serkan; Bozoglan, Alihan; Ozercan, Ibrahim Hanifi (Mdpi, 2025)
Background and Objective: The aim of this study was to evaluate the effects of enamel matrix protein, platelet-rich fibrin (PRF), and bone graft on new bone formation beyond the skeletal system by creating calvarial bone defects in rats. The effects were assessed using histopathological and immunohistochemical analyses. Materials and Methods: In this study, calvarial bone defects were created in male Sprague Dawley rats weighing 500-550 g. The animals were randomly divided into seven groups: Control (n = 13), Emdogain (EMD, n = 13), Emdogain + Bone Graft (EMD + BG, n = 13), Platelet-Rich Fibrin (PRF, n = 13), PRF + Bone Graft (PRF + BG, n = 13), Bone Graft (BG, n = 13), and PRF + Emdogain + Bone Graft (PRF + EMD + BG, n = 13). An additional group of 36 rats was used for PRF preparation. Titanium domes were placed on the calvarial bone defects, and the animals were sacrificed after three months. Bone samples were evaluated histopathologically for new bone formation, numbers of osteoblasts and osteoclasts, angiogenesis, and fibrosis. Immunohistochemical analysis of bone formation was performed using OPG and RANKL staining kits. Data were analyzed statistically. Results: The PRF group showed a significantly higher level of moderate new bone formation compared with the PRF + BG, EMD + BG, and PRF + EMD + BG groups (p <= 0.05). No significant differences were observed among the groups in terms of fibrosis or angiogenesis (p > 0.05). Similarly, OPG and RANKL levels, as well as the OPG/RANKL ratio, did not differ significantly between groups (p > 0.05). Conclusions: Based on the findings of this study, the combined use of Emdogain, PRF, and bone graft appears to have beneficial effects on enhancing bone formation in calvarial defects.
Keywords: enamel matrix protein; guided tissue regeneration; platelet-rich fibrin; titanium; membrane; Xenograft; OPG; RANKL; model antitumor assays